Accumulation by dispossession and electoral democracies: An analysis of land acquisition for special economic zones in India - Kartik Misra (University of Massachusetts, Department of Economics, 2019)
Forcible acquisition of agricultural land to facilitate accumulation by dispossession attempts like setting up of Special Economic Zones (SEZ) is fiercely resisted by farmers in India. These agita- tions may determine the political viability of governments. The ability if the state to enact and implement policies favoring accumulation by dispossession is determined by the political con ict between, on the one side, the elite and the state, and, on the other side, dispossessed farmers and landless agricultural workers. The outcome of this con ict is determined by the distribution of power in society and the success of different groups in mobilizing and enforcing their class interests. Using a simple model of the political con ict over land acquisition and new data-set on SEZs that failed to acquire land from farmers, this paper shows that factors like inequality in land ownership (class) and hierarchies of caste and gender hinder the ability of small and marginal farmers from protecting their class interests even though they have de jure political rights and majority in the voting process. Further, excessive political competition along caste and ethnic lines weakens the political power of farmers and reduces the probability of success of farmer movements. Finally, the promise of formal employment and higher wages does not convince marginalized communities or educated farmers to support SEZs.
Keywords: 330